Summary Indicators of Product Market Regulation with an Extension to Employment Protection Legislation - Nicoletti, Giuseppe (OECD Economics Department Working Papers, 2000)
This paper presents a database on indicators of product market regulations and employment protection legislation for most of the OECD countries and illustrates a methodology for aggregating these detailed indicators into summary indicators of the strictness of regulations. The summary indicators are obtained by means of factor analysis, in which each component of the regulatory framework is weighted according to its contribution to the overall variance in the data. These indicators are used to assess the regulatory approaches across countries as well as the interrelations between various sets of regulatory provisions. While regulatory provisions can be classified and assessed from a variety of standpoints, this paper focuses exclusively on the relative friendliness of regulations to market mechanisms: there is no attempt to assess the overall quality of regulations or their aptness in achieving their stated public policy goals. The guiding principle inspiring the conception of the ...